If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=-7(x+3)
We move all terms to the left:
7-(-7(x+3))=0
We calculate terms in parentheses: -(-7(x+3)), so:We get rid of parentheses
-7(x+3)
We multiply parentheses
-7x-21
Back to the equation:
-(-7x-21)
7x+21+7=0
We add all the numbers together, and all the variables
7x+28=0
We move all terms containing x to the left, all other terms to the right
7x=-28
x=-28/7
x=-4
| (x-17)×(8-2x)=0 | | 5m+5=-90 | | 7-5+3x-1=8x+3 | | 4=3+x/4 | | 7-5+3x-1=7x-1 | | 9+2(x-9)=10-5(x-6) | | 8y+3=5y+5 | | 7w=896 | | 1+2n=9+3n | | 2-(7x+2)=5-x | | 2+8x=6x+6 | | 13y/28-4=5-7y/4 | | 6m+16=m+1 | | 2/3z=15 | | 10+3m=6+2m | | 76=4(8)(2)+2(2)(h) | | 6(x-5)+18=6x-14 | | 1+x=15+3x | | 200+24+m=1845 | | 2(x-8)+13=2x-3 | | 4.50x=12 | | 1-7p=-5-6p | | 100+12+m=1229 | | 2x-5=2(x-1)+11 | | 50/x=12 | | T+2=-7t+2 | | 9x+7=9x+9 | | 17x+11+67=180 | | 3/15=12/x | | 0+m+6=369 | | -4(3-x)=0.8(x+17) | | 2/9x+1/9=7/9 |